2009
DOI: 10.1007/s11999-009-1038-9
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Head Size and Wear of Highly Cross-linked Polyethylene at 5 to 8 Years

Abstract: Wear of highly cross-linked polyethylene is reportedly independent of head size. To confirm that observation we asked in our population whether head size related to wear with one type of electron beam highly cross-linked polyethylene. Of 146 hips implanted, we evaluated complete clinical and radiographic data for 90 patients (102 hips or 70%). The minimum followup was 5 years (mean, 5.7 years; range, 5-8 years). The head size was selected intraoperatively based on the size of the acetabular component and presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 32 publications
(59 reference statements)
3
93
2
3
Order By: Relevance
“…The clinical studies of the wear of this XLPE with large femoral heads reported low linear wear rates at 3 to 7 years [2][3][4]7]. Our previous study using the titanium fiber-metal acetabular component and this XLPE showed low linear wear and no osteolysis at 5 to 8 years followup, but there was more volumetric wear in those hips with 36-and 40-mm femoral heads [15]. There are few studies of XLPE with 10-year followup time, but these are limited by small numbers of patients and different wear measurement techniques [1,8,11,13,25].…”
Section: Introductionmentioning
confidence: 67%
“…The clinical studies of the wear of this XLPE with large femoral heads reported low linear wear rates at 3 to 7 years [2][3][4]7]. Our previous study using the titanium fiber-metal acetabular component and this XLPE showed low linear wear and no osteolysis at 5 to 8 years followup, but there was more volumetric wear in those hips with 36-and 40-mm femoral heads [15]. There are few studies of XLPE with 10-year followup time, but these are limited by small numbers of patients and different wear measurement techniques [1,8,11,13,25].…”
Section: Introductionmentioning
confidence: 67%
“…[15,35] More recent studies of 28 and 32 mm femoral heads articulating with HXPLE show a low incidence of osteolysis with less than 0.1 mm per year (62 and 80 mm 3 per year) of wear. [22,28,32] However, when discussing "wear" in regards to larger femoral heads on HXLPE, surgeons, and manufacturers should focus on decreasing volumetric wear, since laboratory analysis has shown linear wear of HXLPE is independent of head size [31]. A 4-year study [22] analyzing wear rates of HXLPE using 28, In a similar study looking at wear rates of HXLE using 26, 28, 32, 36, and 40 mm femoral heads at 5-8 years after surgery, Lachiewicz et al [28] published the median linear wear rate of all components was 0.028 mm/year (mean, 0.04 mm/year), and the median volumetric wear rate was 25.6 mm 3 /year (mean, 80.5 mm 3 /year).…”
Section: Resultsmentioning
confidence: 99%
“…[22,28,32] However, when discussing "wear" in regards to larger femoral heads on HXLPE, surgeons, and manufacturers should focus on decreasing volumetric wear, since laboratory analysis has shown linear wear of HXLPE is independent of head size [31]. A 4-year study [22] analyzing wear rates of HXLPE using 28, In a similar study looking at wear rates of HXLE using 26, 28, 32, 36, and 40 mm femoral heads at 5-8 years after surgery, Lachiewicz et al [28] published the median linear wear rate of all components was 0.028 mm/year (mean, 0.04 mm/year), and the median volumetric wear rate was 25.6 mm 3 /year (mean, 80.5 mm 3 /year). The authors found no association between femoral head size and the linear wear rate, but observed an association between larger (36 and 40 mm) head size and increased volumetric wear rate and total volumetric wear ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Hammerberg et al [58] reported a linear penetration rate after an average 3.6-year followup of 0.023 and 0.021 mm/year for 28-to 32-mm and 38-to 44-mm femoral heads on Durasul 1 liners. With a longer mean followup time of 5.7 years, Lachiewicz et al [83] reported linear penetration rates of 0.06, 0.032, 0.011, and 0.075 mm/year for 26-, 28-, 32-, and 36-to 40-mm heads, respectively, on Longevity 1 liners. An RCT by Bragdon et al [21] reported linear penetration rates of 0.020 and 0.005 mm/year for 28-and 38-mm heads, respectively, with Durasul 1 and Longevity 1 liners after a followup of 6.9 years.…”
Section: Systematic Review Of Femoral Head Penetration Studies For Hxmentioning
confidence: 99%